Challenges parents face in learning Kenyan Sign Language: Hearing parents of deaf children's perspectives - and Luchivya, Rosemary; Omolo, Tom; Onditi, Sharon (African Journal of Education and Practice, 2020)
Purpose: The purpose of this study was to find out the challenges faced in learning Kenyan sign language from the perspective of hearing parents of deaf learners. Methodology: This study employed case study design, qualitative research approach adopting the interpretive paradigm. The study adopted purposive sampling technique to come up with a study sample of 177 informants. Data was collected using interview schedules, Focus Group Discussion guides and Document analysis guide. Qualitative data was transcribed, coded and organized into themes and reported. Findings: Results revealed that parents had three major challenges in learning Kenyan sign language: that Kenyan sign language was too difficult to learn, it was too costly to learn and that the institutions for parents to learn in were not readily available. Unique contribution to theory, practice and policy: The recommendations of this study were that; hearing parents of children with hearing impairments be given support in the process of learning Kenyan sign language and that parents should make deliberate efforts to learn Kenyan sign language and other modes of communication in order to communicate with their children with hearing impairments.